2020
DOI: 10.1007/s11356-020-11776-y
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen removal performance and bacterial communities in zeolite trickling filter under different influent C/N ratios

Abstract: In this study, the degradation performance of nutrients in zeolite trickling filter (ZTF) with different influent C/N ratios and aeration conditions was investigated. Microaeration was beneficial for enhancing NH 4 + -N removal performance. Due to the sufficient carbon source supply under a C/N ratio of 8, a high removal efficiency of NH 4 + -N and TN was simultaneously observed in ZTF. In addition, TN removal mainly occurred at the bottom, which might be explained by the sufficient nutrients available for bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…At the same time, Acinetobacter (5.5%), Paracoccus (2.0%), and Pseudomonas (5.9%) were found in EFW to simultaneously oxide organic matter and oxide ammonia to nitrite and nitrate, which were denitrified to N 2 under the aerobic condition [ [49] , [50] , [51] , [52] ]. For instance, Gu et al.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, Acinetobacter (5.5%), Paracoccus (2.0%), and Pseudomonas (5.9%) were found in EFW to simultaneously oxide organic matter and oxide ammonia to nitrite and nitrate, which were denitrified to N 2 under the aerobic condition [ [49] , [50] , [51] , [52] ]. For instance, Gu et al.…”
Section: Resultsmentioning
confidence: 99%
“…The TN removal rate increased by 31.9% in system E compared to system A, as a joint result of the zeolite substance layer and electrolysis. Electrolysis could prolong the service life of zeolite and enhance the biological regeneration by affecting the ionexchange process and biochemical reactions of microorganisms, which can achieve the sustainable utilization of zeolite and reduce the operation cost of system E. 12 TN removal rates increased throughout the experimental period (120 days) of system E, from 45.6 ± 20.4% (phase I) to 90.4 ± 1.6% (phase III), and the effluent TN concentration reduced to 2.7 mg/L, consistently meeting the standards for drinking water quality (GB 5749-2006) (Table S9). 13 NO 3 − -N removal performance was similar to that of TN during the entire period (Figure 1d).…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, the relative abundance of Actinobacteria in the CW_C treatment also significantly decreased at both the fore and rear ends of HSSFCWs. Previous studies indicated that Actinobacteria and Acidobacteria were key species in the transformation of carbon and nitrogen in CWs [42]. Earlier research had noted that Acidobacteria was involved in litter decomposition [43], while Actinobacteria played a role in the process of denitrification [24].…”
Section: Bacterial Community Compositionmentioning
confidence: 99%